MANAJEMEN LABA PADA PERUSAHAAN BASIC MATERIAL - Faisal, Yusuf; Oktaviani, Resty Fuji; Sari, Egi Gumala (UNIVERSITAS DHARMAWANGSA, 2024)
This research was conducted ti observing 98 basic material listed on the Indonesia Stock Exchange. The data source used is the company’s annual report from 2012-2022. This study aims to obtain empirical evidence on the influence of intellectual capital , tax planning , and leverage with institutional ownership as a moderating variable. The result of this study found that intellectual capital has a positive and statistically effect on earnings management, while tax planning has a positive and statistically insignificant effect on earnings management, leverage has a positive and statically insignificant effect on eanings management. Furthermore, institutional ownership strengthens the influence of intellectual capital on earnings management. Institutional ownership weakens the influence of tax planning on earnings management. Institutional ownership also reinforces the effect of leverage on earnings management.